2013
DOI: 10.1021/am403720r
|View full text |Cite
|
Sign up to set email alerts
|

Porous Fluorine-Doped γ-Fe2O3 Hollow Spheres: Synthesis, Growth Mechanism, and Their Application in Photocatalysis

Abstract: Porous fluorine-doped maghemite(γ-Fe2O3) hollow spheres have been prepared by facile route based on solvothermal reaction and sequential calcinations. The composition and morphology of the as-prepared samples were characterized by various techniques. The SEM and TEM results showed that the as-synthesized products exhibited a spherical morphology with porous hollow structures. Ultraviolet-visible (UV-vis) diffuse reflectance spectra display that the optical performance of γ-Fe2O3 products are related to their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…The TiO 2 with daisy‐like and spherical structure yield the lower band gap energy. In previous report by Zhu et al., the band gap energies of semiconductor nano‐materials were much depended on their structures. TiO 2 particles with nanoburrs or lateral organization were inclined to produce lower band gap energy …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The TiO 2 with daisy‐like and spherical structure yield the lower band gap energy. In previous report by Zhu et al., the band gap energies of semiconductor nano‐materials were much depended on their structures. TiO 2 particles with nanoburrs or lateral organization were inclined to produce lower band gap energy …”
Section: Resultsmentioning
confidence: 96%
“…Compared to TiO 2 ‐SL, the other three TiO 2 exhibits a much stronger adsorption in the UV‐visible range of 200–800 nm. Calculation using Kubelka–Munk method based on the diffuse reflectance spectra could obtain the relative band gap of TiO 2 synthesized . As shown in Figure b, the band gap energy Eg can be calculated by the Tauc plots (αhν) 2 and hν relationship .…”
Section: Resultsmentioning
confidence: 99%
“…Their physicochemical properties can be driven by particle size distribution and morphology of the as‐prepared materials. So far, it has been reported that among electric properties, it is also possible to change magnetic properties, photocatalytic activity, and features for targeted drug delivery application easily by the shape of nanoparticles. The type of morphology is related to the surface area; intrinsic morphology can considerably increase the accessible surface, thus offering a large capacity for loading various compounds and ions (e.g., in lithium‐ion batteries) …”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort has been devoted to the morphology-controllable synthesis of ZnO [3]. In our previous works, we reported the control synthesis of semiconductor metal oxide using different methods [4][5][6][7][8][9][10][11][12]. One of the most promising methods is a biomimetic strategy that uses surfactants or polymers as the structuredirecting agent to control the nucleation, growth, and alignment of crystals [3].…”
Section: Introductionmentioning
confidence: 99%